Molecular Self-Assembly Enables Tuning of Nanopores in Atomically Thin Graphene Membranes for Highly Selective Transport - Jang, Doojoon; Bakli, Chirodeep; Chakraborty, Suman; Karnik, Rohit (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2022)
Atomically thin membranes comprising nanopores in a 2D material promise to surpass the performance of polymeric membranes in several critical applications, including water purification, chemical and gas separations, and energy harvesting. However, fabrication of membranes with precise pore size distributions that provide exceptionally high selectivity and permeance in a scalable framework remains an outstanding challenge. Circumventing these constraints, here, a platform technology is developed that harnesses the ability of oppositely charged polyelectrolytes to self-assemble preferentially across larger, relatively leaky atomically thin nanopores by exploiting the lower steric hindrance of such larger pores to molecular interactions across the pores. By selectively tightening the pore size distribution in this manner, self-assembly of oppositely charged polyelectrolytes simultaneously introduced on opposite sides of nanoporous graphene membranes is demonstrated to discriminate between nanopores to seal non-selective transport channels, while minimally compromising smaller, water-selective pores, thereby remarkably attenuating solute leakage. This improved membrane selectivity enables desalination across centimeter-scale nanoporous graphene with 99.7% and >90% rejection of MgSO4 and NaCl, respectively, under forward osmosis. These findings provide a versatile strategy to augment the performance of nanoporous atomically thin membranes and present intriguing possibilities of controlling reactions across 2D materials via exclusive exploitation of pore size-dependent intermolecular interactions.